Verres incolores de l'antiquité romaine en Gaule et aux marges de la Gaule - Foy, Danièle, (Archaeopress Roman archaeology ;, 2018)
Colourless glass became prominent between the middle of the 1st century AD and the beginning of the 4th century. This text reflects the diversity of glass and is designed as a practical manual divided into three parts: assemblages, typological catalogue, chemical analyses.